2016
DOI: 10.1126/science.aaf6005
|View full text |Cite
|
Sign up to set email alerts
|

Phytochromes function as thermosensors inArabidopsis

Abstract: Plants are responsive to temperature, and can distinguish differences of 1ºC. In Arabidopsis, warmer temperature accelerates flowering and increases elongation growth (thermomorphogenesis). The mechanisms of temperature perception are however largely unknown. We describe a major thermosensory role for the phytochromes (red light receptors) during the night. Phytochrome null plants display a constitutive warm temperature response, and consistent with this, we show in this background that the warm temperature tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
752
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(829 citation statements)
references
References 42 publications
29
752
0
8
Order By: Relevance
“…In addition, phyB was shown to interact with EBF1/2 to promote the degradation of EIN3 (45). Given the recent finding that phyB is a thermosensor of ambient temperature (13,14), it will be intriguing to explore whether phyB also serves as a cold sensor that mediates the EBF1/2-PIF3-CBF pathway.…”
Section: Fig 3 Ebf1 Is a Positive Regulator Of Freezing Tolerance mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, phyB was shown to interact with EBF1/2 to promote the degradation of EIN3 (45). Given the recent finding that phyB is a thermosensor of ambient temperature (13,14), it will be intriguing to explore whether phyB also serves as a cold sensor that mediates the EBF1/2-PIF3-CBF pathway.…”
Section: Fig 3 Ebf1 Is a Positive Regulator Of Freezing Tolerance mentioning
confidence: 99%
“…Intriguingly, two recent reports demonstrated that phyB acts as a thermosensor of ambient temperature (13,14), but the precise role of phytochromes in the cold stress response awaits further investigation. CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1) and ELONGATED HYPOCOTYL 5 (HY5), two central regulators of photomorphogenesis, have been shown to integrate light and cold signaling to optimize plant survival under freezing temperatures (15).…”
mentioning
confidence: 99%
“…PIFs are regulated by light, temperature, and the circadian clock, and these cues can lead to PIF degradation by concerted action of the PHYs and the E3-ligase LightResponse Bric-a-Brack/Tramtrack/Broad (Leivar and Monte, 2014;Ni et al, 2014;Jung et al, 2016;Legris et al, 2016). The PHY and CRY photoreceptors can physically interact with specific sets of PIF proteins and thereby regulate PIF phosphorylation.…”
Section: Pifsmentioning
confidence: 99%
“…Phytochromes sense light by switching between an inactive and active form. Warm temperatures deplete the active phytochrome pool and disrupt the transcriptional output of phytochrome B signaling (Jung et al, 2016;Legris et al, 2016). In this way, temperature information is perceived and transduced through the light-sensing pathway to regulate thermomorphogenesis.…”
mentioning
confidence: 99%
“…Thermosensing is an important function of the red-light photoreceptor phytochrome B in Arabidopsis, particularly at night (Jung et al, 2016;Legris et al, 2016). Phytochromes sense light by switching between an inactive and active form.…”
mentioning
confidence: 99%